Modeling and simulation of porous journal bearings in multibody systems - Buuren, Sietze van (Schriftenreihe des Instituts für Technische Mechanik, Karlsruher Institut für Technologie, 2013)
A specific cost-efficient type of plain journal bearing is the porous journal bearing, which possesses a pervious bush that serves as a lubricant reservoir. The current work is concerned with modeling porous journal bearings in multibody systems, for which dynamical models are needed to investigate the bearing’s behavior. Such porous journal bearing models as well as models of elementary rotor-bearing systems including these, were developed and investigated during the course for this work.